Math, asked by vg8924905451, 7 months ago

Find the value of the expression a² – 2ab + b² for a = 1, b = 1

Answers

Answered by pulakmath007
10

SOLUTION :-

TO DETERMINE :-

The value of the expression

 \sf{ {a}^{2} - 2ab +  {b}^{2}  } for a = 1 , b = 1

EVALUATION :-

PROCESS : 1

Here the given expression is

 \sf{ {a}^{2} - 2ab +  {b}^{2}  }

Putting a = 1 & b = 1 we get the value of the expression

 =  \sf{ {(1)}^{2} - 2.1.1 +  {(1)}^{2}  }

 =  \sf{ 1 - 2 + 1  }

 \sf{ = 0}

PROCESS : 2

USING IDENTITY

We are aware of the identity that

 \sf{ {a}^{2} - 2ab +  {b}^{2}  } =  {(a - b)}^{2}

Hence the value of the expression

 =  \sf{ {a}^{2} - 2ab +  {b}^{2}  }

 =  \sf{ {(a - b)}^{2}  }

 \sf{ =  {(1 - 1)}^{2}   }

 \sf{ =  {(0)}^{2} }

 = 0

━━━━━━━━━━━━━━━━

Learn more from Brainly :-

1. Find a number whose 6 1/4% is 12

https://brainly.in/question/24604085

2.  If HCF of two numbers be 40 then which of the following cannot be their LCM.

https://brainly.in/question/28609013

Answered by hiiiiiiiiiiiiiiii46
6

Answer:

Answer is 0

Step-by-step explanation:

Please refer the attachment for steps

Please mark me as brainalist

Attachments:
Similar questions